Characterizing the Application of Mathematical Thinking in Citizen Science - Gonzales, Abigail B.; Joaquin, Ma. Nympha B.; Monterola, Sheryl Lyn C. (Philippine Journal of Education Studies (formerly the Education Quarterly); Vol 1 No 1 (2023), 2024)
Mathematical thinking is important for citizens to develop not only for academic purposes but also more importantly for participating responsibly in society. This paper describes the features of the application of mathematical thinking processes in citizen science. Mathematical thinking involves processes such as problem-solving, reasoning and proof, communication, connections, and representation. Citizen science, on the other hand, is an emerging research activity in which the public can participate. In contrast to conventional science, individuals in citizen science participate in research activities rather than as subjects of study. Purposive sampling and a grounded theory approach were used in this investigation. In this study, 15 citizen science projects were considered as the sample. The findings suggest that problem-solving and connection are the most commonly practiced mathematical thinking processes in citizen science. Furthermore, the study reveals that individuals involved in citizen science demonstrate problem-solving, reasoning and proof, communication, and representation as primary tasks in the various research activities. Connection, on the other hand, is mostly used as a subprocess. These findings suggest that persons engaged in citizen science can execute all mathematical thinking processes. However, among these processes, problem-solving is the most widely implemented and hence most developed through citizen science.